Itacuruba ontem e hoje: novos tempos, novos espaços: uma questão identitária - Simões, Deysiane Ribeiro Pessoa (2017)
Considering the scarcity of scientific publications of Psychology in Portuguese about the relation of the human being with the new information and communication technologies, this master's research intends to investigate the possibilities that this new culture promotes for a work of identity significance. We are interested in the young population of the city of Itacuruba, which is located in the micro-region of the hinterland of São Francisco's river, flooded in 1988 for the construction of the Itaparica dam. Its population began to live in a newly constructed city and to experience a reality of adaptation due to the losses left by the extinction of its constituent place. The new configuration led to important changes in the field of the identity dimension of these people. Not only the city was submerged, but the history of each inhabitant. Moreover, for a while, a growing state of illness in the new city could be identified, with an increasement of cases of depression and suicides. This situation affected mainly the young population. At the same time, the use of the resources of information and communication technologies was increasing in the world scenario, allowing the breaking of borders and new forms of relations. A generation belonging to this digital universe was born, which began to circulate through cyberspace in a fluid way and to construct new modalities and expressions of identity in it. Therefore, the main objective of this research is to analyze how the use of the New Information and Communication Technologies favors the elaboration of the identity issue of the young people of Itacuruba, in their relationship with the city. And the secondary objectives are to analyze in which way the reference of the old city exists for the young people who live today in Itacuruba; to verify how digital technologies are used for the young people under study; and to understand how social networks have modified the lives of young people in Itacuruba. In order to elucidate this study, it was used a theoretical reference that works on the identity theme based on Social Psychology, Psychoanalysis and Cyberpsychology; conceptualizing and contextualizing the relationships that take place in cyberspace. The methodology of the research is qualitative and includes a work of Netnography, method of research applied to the environment of new technologies, developed in person and through technological support for observation of the field of research and access to the participants through semi-structured interviews. The data processing resource was the content analysis, proposed by Bardin. And as a result it was evidenced that there is a significant presence of new technologies in the daily life of young people in the city, so that this universe starts to produce a new system of references to live in Itacuruba.